Predictive analysis of osteoarthritis and chronic pancreatitis comorbidity: complications and risk factors - Halabitska, Iryna; Petakh, Pavlo; Oksenych, Valentyn; Kamyshnyi, Oleksandr (Frontiers in Endocrinology, 2024)
Background. The comorbidity of chronic pancreatitis (CP) in patients with osteoarthritis (OA) is insufficiently studied, and the reciprocal impact of these conditions remains poorly understood. This study aimed to investigate potential predictors for the development of CP in OA patients, as well as associated complications. Methods. A cohort of 181 patients was categorized into four groups: a control group (n=30), patients with OA (n=68), patients with CP (n=31), and patients with OA and comorbid CP (n=52). All four groups had no statistical differences in age and gender. The study utilized the WOMAC index, Visual Analog Scale (VAS), Lequesne index, biochemical assays, and advanced statistical methods to assess joint status in OA patients with comorbid CP. It explored potential predictors of comorbidity development and associated complications. Results. The study revealed that concurrent CP in OA exacerbates progression and contributes to malnutrition. Body Mass Index (BMI) emerged as a potential predictor for CP comorbidity development in OA patients. Factors such as the WOMAC total score, fecal elastase-1, C-reactive protein (CRP), ferritin, retinol, tocopherol, 25hydroxyvitamin D3, and BMI were found to influence the development of comorbidity of CP in OA. Additionally, Gastrointestinal Symptom Rating Scale-Diarrhea Syndrome (GSRS-DS), Gastrointestinal Symptom Rating Scale-Constipation Syndrome (GSRS-CS), Qualitative Assessment of the Symptoms and Impact of Pancreatic Exocrine Insufficiency Domain A (PEI-Q-A), retinol, tocopherol, and iron were identified as potential predictors comorbidity CP with exocrine pancreatic insufficiency in OA patients. Сonclusion. The presence of CP in OA patients exacerbates disease progression and complications, necessitating further investigation.